KEDUDUKAN ANAK ANGKAT DALAM HUKUM WARIS ISLAM DI WILAYAH HUKUM PENGADILAN AGAMA KOTA JAMBI - Abdul Hariss; , Nurfauzia (Jurnal LEX SPECIALIS, 2010)
AbstractIn the area of Jambi known also foster child. Foster child is a child who clearly origins appointed with the consent of the family of both parties and confirmed by the village head.Adopted children are urgently needed in domestic life that has no biological children and is considered as a child of their own children, but in the future after the adult child or the adoptive parents already have a biological child or the adoptive parents died arise various problems of foster child, both at the time to establish a marriage or in terms of inheritance In Islamic law which is used as the foundation of society customary inheritance law does not define the city of Jambi's adopted son as heir adoptive parents, but in reality there that give step-son inheritance, although eventually when there will be a problem.